Perlindungan Lingkungan dalam Hukum Humaniter - Wartini, Sri (Jurnal Hukum IUS QUIA IUSTUM, 2006)
War has never been kind to human environment and human health. Trough out history, warfare hasbeen associated with death, disease, pollution and destruction of the environment The Human Rights Law and Humanitarian Law does not protect the Environment directly, so that the protection of those isstill weak